ANALISIS DAMPAK LINGKUNGAN BELAJAR TERHADAP RENDAHNYA PEMAHAMAN KONSEP MATEMATIKA PADA MATERI ALJABAR SISWA SMP - Nurhana; Usman Mulbar (Universitas Nias Raya, 2025)
This study aims to conduct an in-depth analysis of the impact of the learning environment on students’ low understanding of mathematical concepts, particularly in algebra topics among junior high school students. The learning environment is an essential factor that plays a major role in determining students’ success in comprehending abstract mathematical concepts that require logical thinking skills. This research employs a theoretical review or literature study method by examining various scholarly sources such as journals, books, and previous research findings relevant to the topic. Data collection techniques were carried out through analysis, comparison, and synthesis of information from various references. The results of the study indicate that the condition of the learning environment, both physical and non-physical, has a significant influence on students’ understanding of algebraic material. Factors such as classroom noise, inadequate lighting, limited learning facilities, low motivation, and less conducive social interactions have been proven to reduce students’ concentration and interest in learning mathematics. Therefore, it can be concluded that efforts to improve students’ understanding of mathematical concepts must be accompanied by creating a comfortable, interactive, and creative learning environment that motivates students to think critically and participate actively in the learning process.